The Paradox of Transgender: A Case Study of District Faisalabad - Dr. Sidra Akram; Muhammad Sufyan Fiaz; Dua Athar (`, 2025)
Gender refers to the many ways we describe human sex traits. It helps us distinguish between men and women. Transgender describes people whose gender identity differs from their birth sex. They do not fit into male or female categories. Some individuals choose to live as transgender, modifying their lives accordingly. This paper explores the challenges faced by this group in Pakistan. The study highlights how the government fails to implement laws passed for this marginalised section of society. There is a need to provide health, education, and financial opportunities for this community. The primary focus of this study is to analyze the socio-economic challenges faced by transgender individuals and their living patterns in the Faisalabad district. The research employs a mixed-method approach. Both qualitative and quantitative research designs were adopted, involving semi-structured in-depth interviews. The researchers successfully conducted interviews with 15 transgender individuals. The results indicate that their marginalised status is mainly due to a lack of governmental support. Keywords: Gender, Paradoxes, Transgender, Marginalised Community